High Incidence of Herpes Simplex Virus-1 in Cord Blood and Placenta Infection of Women in Southern Brazil - Emiliana Claro Avila; Fabiana Finger-Jardim; Carla Vitola Gonçalves; Vanusa Pousada da Hora; Marcelo Alves Soares; Ana Maria Barral de Martínez (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective Estimate the prevalence of human herpesvirus type 1 HSV-1 DNA in placental samples, its incidence in umbilical cord blood of newborns and the associated risk factors. Methods Placental biopsies and umbilical cord blood were analyzed, totaling 480 samples, from asymptomatic parturients and their newborns at a University Hospital. Nested polymerase chain reaction (PCR) and gene sequencingwere used to identify the virus; odds ratio (OR) and relative risk (RR) were performed to compare risk factors associated with this condition. Results The prevalence of HSV-1 DNA in placental samples was 37.5%, and the incidence in cord blood was 27.5%. Hematogenous transplacental route was identified in 61.4% from HSV-1+ samples of umbilical cord blood paired with the placental tissue. No evidence of the virus was observed in the remaining 38.6% of placental tissues, suggesting an ascendant infection from the genital tract, without replication in the placental tissue, resulting in intra-amniotic infection and vertical transmission, seen by the virus in the cord blood. The lack of condom use increased the risk of finding HSV-1 in the placenta and umbilical cord blood. Conclusion The occurrence of HSV-1 DNA in the placenta and in cord blood found suggests vertical transmission from asymptomatic pregnant women to the fetus.